The Students’ Difficulties in Writing Short Functional Text at The Eleventh Grade Students of SMA Negeri 1 Siborongborong - Siahaan, Rekolina; Situmeang, Lamhot Martua; Hutabarat, Novita C. (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to know the dominant difficulty and cause of difficulty. Difficulty is the trouble or effort that something involves, mistakes, difficult thing to do or deal with. To find students’ difficulties in writing short functional text , this study was conducted by applying descriptive qualitative research. The subject was the eleventh grade of SMA Negeri 1 Siborongborong. There were 22 respondents as subject at the eleventh grade of student. To collect the data, the writer used test, questionnaire, and interview. The number of item were 12 that done by giving questionnaire and interview. After collecting data, they were analyzed . Having analyzing the data, writer finally could range the dominant difficulty. As the finding that students’ dominant difficulty in writing short functional text is the language use aspect with 68 % frequent errors of tenses, number, word order/function, meaning confused or obscured. Difficulty of language use in writing because they don’t understand about tenses that is stated by 57 % respondents.